Utilizing the Concept of Convenience as a Business Opportunity in Emerging Markets - Sundström, Malin; Radon, Anita (Organizations and Markets in Emerging Economies, 2016)
Non-store retailing is dominated by the Internet and is a potential strategy for manufacturers, brand owners, and retailers entering emerging markets. Consumers in developed markets shop online for a variety of retail goods, and motives for choosing e-commerce are often referred to as convenience reason. Convenience is essential for understanding why consumers prefer one channel to another. By revisiting the concept of convenience as a significant variable in e-commerce and exploring its complexity and the multiple meanings of the concept with regard to emerging markets, the paper considers a business opportunity in terms of new ways of reaching emerging markets and proposes potential lines for future research with regard to this concept.